2020
DOI: 10.1080/09553002.2020.1770360
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic exposure to a magnetic field on energy metabolism and locomotion of Blaptica dubia

Abstract: Purpose: This study deals with a comparative analysis of the effects of chronic exposure to a static magnetic field (SMF) and an extremely low frequency magnetic field (ELF MF) in Blaptica dubia nymphs. The outcome of such treatment on insect and fat body mass, glycogen and total lipid content in the fat body and locomotion, as an energy demanding process, were examined.Materials and methods: One-month-old nymphs of B. dubia were exposed to an SMF (110 mT) or ELF MF (50 Hz, 10 mT) for 5 months. Their locomotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…Todorovic et al . (2020) also found that exposure to MF can alter insect energy metabolism pathways to cope with external stressors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Todorovic et al . (2020) also found that exposure to MF can alter insect energy metabolism pathways to cope with external stressors.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the up-regulation of pyruvic acid signifies a substantial alteration in shrimp metabolism, indicating notable changes in the utilisation of nutrients for energy production and other metabolic processes. Todorovic et al (2020) also found that exposure to MF can alter insect energy metabolism pathways to cope with external stressors.…”
Section: Organic Acids and Derivativesmentioning
confidence: 90%
“…They have a neuromodulatory role and mobilize internal fuel reserves and stimulate insect locomotor activity. AKHs also have a metabolic role and control the release of carbohydrates, lipids, and the amino acid proline from the body fat to the heamolymph during locomotion and flight locomotion [62,67,68]. Earlier studies have demonstrated the impact of both an SMF and EMF on BA concentrations in crickets, cockroaches, and fruit flies, as well as on the activity of neurosecretory neurons in gypsy moth caterpillars and yellow mealworm pupae [25,26,[69][70][71].…”
Section: Discussionmentioning
confidence: 99%